Intermezzo / Sally Rooney. - Rooney, Sally (Faber, 2025)
Aside from the fact that they are brothers, Peter and Ivan Koubek seem to have little in common. Peter is a Dublin lawyer in his 30s - successful, competent and apparently unassailable. But in the wake of their father's death, he's medicating himself to sleep and struggling to manage his relationships with two very different women - his enduring first love Sylvia, and Naomi, a college student for whom life is one long joke. Ivan is a 22-year-old competitive chess player. He has always seen himself as socially awkward, a loner, the antithesis of his glib elder brother. Now, in the early weeks of his bereavement, Ivan meets Margaret, an older woman emerging from her own turbulent past, and their lives become rapidly and intensely intertwined.